Algunas ideas sobre el concepto de conciencia: Por una relación dialéctica entre el ser humano y el mundo. (2021)
This present article is to involve dialectically, an affair relationship between human condition and its experience through the world by granting to the conscience concept, a fundamental place when it comes for realizing about objective and subjective world. This text’s reflections are built up on an anthropologicontological basis whereas the human being is the one who grounds - throughout his existence vicissitudes – the very best willing ways to understand the world and his world. An “I” that can speak out on demanding: “I think, “I am” as a being frame to can its own existence in a world which demands braveness, prudence, action and thinking as well. This one written, pretends to identify the given “consciousness levels” on a triple subject-object affair - framed in a social logic- which are to be the main premises in order to understand what living in a world is, as the world inhabit in us by a language mean.